Pengoptimalan Pengolahan Air Pada Proses Koagulasi dengan Kombinasi Bahan Kimia Aluminium Sulfat dan Poly Aluminium Chloride PT. Tirta Sriwijaya Maju (Perseroda) Palembang - Muhajir, Ahmad; Junaidi, Robert; Aznury, Martha (Innovative: Journal Of Social Science Research, 2024)
PT Tirta Sriwijaya Maju (TSM) is a clean water provider company operating in Palembang City. The TSM Water Treatment Plant (WTP) processes surface water from the Musi River with a total capacity of 230 liters/second. However, the TSM WTP is facing a shortage of clean water supply due to an increase in demand from new customers. This has led to a decrease in the duration of water flow to customers' homes. This problem is caused by 5% of the byproducts being sludge and wastewater, as well as the filter washing process that causes production to stop for 30 minutes three times a day. Therefore, this study aims to analyze the use of a combination of aluminum sulfate and poly aluminum chloride coagulants to reuse the sludge and minimize filter washing, in order to improve water treatment performance at the TSM WTP. The analysis results show that the alum and PAC dose ratio of 3:1 and 4:1 produced the highest turbidity reduction, which are 85.1% and 91.3%, as well as good floc formation. Thus, the use of this coagulant combination can be a solution to increase the productivity of the TSM WTP in providing sustainable clean water supply.